2019
DOI: 10.1038/s41419-019-1839-z
|View full text |Cite
|
Sign up to set email alerts
|

PUM1 knockdown prevents tumor progression by activating the PERK/eIF2/ATF4 signaling pathway in pancreatic adenocarcinoma cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a malignant tumor with very poor prognosis. Therefore, it is important to fully understand the molecular mechanism underlying its occurrence and development. Pumilio RNA-binding family member 1 (PUM1) has been reported to function as an oncogene in ovarian cancer and nonsmall cell lung cancer. However, its role and mechanism in PDAC have not been fully illuminated. Here, we found that the PUM1 protein levels were higher in PDAC tissues than in adjacent tissues and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Some studies have indicated the promotion of cancer progression by ATF4 12 , 13 , 15 - 17 . In contrast, some studies have shown that ATF4 inhibits cancer progression 9 , 14 . Participation in the regulation of autophagy by ATF4 was reported 26 , and ATF4 also plays a role in sensitivity to chemotherapy 9 , 10 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies have indicated the promotion of cancer progression by ATF4 12 , 13 , 15 - 17 . In contrast, some studies have shown that ATF4 inhibits cancer progression 9 , 14 . Participation in the regulation of autophagy by ATF4 was reported 26 , and ATF4 also plays a role in sensitivity to chemotherapy 9 , 10 .…”
Section: Discussionmentioning
confidence: 92%
“…Zeng's study indicates that ATF4 promotes invasion and progression of breast carcinomas 12 , and Chen's experiments confirmed that ATF4 promotes proliferation and invasion of gliomas 13 . Others have provided evidence of its anti-cancer function 9 , 14 , and Dai proved that ATF4 inhibits the progression of pancreatic cancer 14 . ATF4 participates in the regulation of many molecular pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the PUM1 gene was silenced, the cell proliferation was significantly inhibited [39]. The deletion of PUM1 can decrease the proliferation of MIA, PaCa-2, and PANC-1 cells and promote their apoptosis [40]. Therefore, we speculate that the conserved function of the Puf protein is to promote proliferation.…”
Section: Discussionmentioning
confidence: 88%
“…Several recent studies validate the role of the Pumilio family of RBPs in diverse biological processes in several organisms. Specific mRNA targets of two human Pumilio isoforms (PUM1 and PUM2) include oncogenes, tumor suppressors, and other factors implicated in oncogenic and cell death pathways [24][25][26] . In several organisms, PUM proteins also play a conserved role in stem cell proliferation and selfrenewal [27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%